2019
DOI: 10.1002/hbm.24549
|View full text |Cite
|
Sign up to set email alerts
|

Recursion in action: An fMRI study on the generation of new hierarchical levels in motor sequences

Abstract: Generation of hierarchical structures, such as the embedding of subordinate elements into larger structures, is a core feature of human cognition. Processing of hierarchies is thought to rely on lateral prefrontal cortex (PFC). However, the neural underpinnings supporting active generation of new hierarchical levels remain poorly understood. Here, we created a new motor paradigm to isolate this active generative process by means of fMRI. Participants planned and executed identical movement sequences by using d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 70 publications
3
22
1
Order By: Relevance
“…This division of labor mirrors recent findings in the visual domain with stroke patients (Martins et al 2019) and suggests that future work aiming to probe the role of the IFG and STG in music (or other cognitive domains) should use test paradigms that do not rely solely on a violation/correct discrimination, but rather isolate the generative acts involved in processing and manipulating hierarchical representations (Fitch 2014;Fitch and Martins 2014).…”
Section: Resultssupporting
confidence: 70%
“…This division of labor mirrors recent findings in the visual domain with stroke patients (Martins et al 2019) and suggests that future work aiming to probe the role of the IFG and STG in music (or other cognitive domains) should use test paradigms that do not rely solely on a violation/correct discrimination, but rather isolate the generative acts involved in processing and manipulating hierarchical representations (Fitch 2014;Fitch and Martins 2014).…”
Section: Resultssupporting
confidence: 70%
“…The opposite is true for action execution and somesthesis. These results make the view of a joint neural basis of language and action as proposed earlier (Arbib and Rizzolatti, 1997;Binkofski and Buccino, 2004;Kühn et al, 2013;Martins et al, 2019;Rizzolatti and Arbib, 1998) less likely. Rather, it appears that language and action are supported by distinct neural networks.…”
Section: Differentiating Action and Language Networkmentioning
confidence: 70%
“…Second, since we expected to find convergence in the left IFG, we further assess which domains reliably involve BA44, and we explore the corresponding connectivity network for motor processing seeding in the region. On the basis of previous literature pointing at sub-regional functional differences inside BA44, alongside longstanding interest for action vs. language cognitive representations (Boeckx and Fujita, 2014;Clos et al, 2013;Fadiga et al, 2009;Fujita, 2009;Grafton and Hamilton, 2007;Leung, 2014;Martins et al, 2019;Moro, 2014bMoro, , 2014aPritchett et al, 2018;Pulvermüller, 2014), we also contrast the observed connectivity network for motor processing in the area against the network seeding in the anterior-ventral BA44. This cluster has been independently shown to be strongly associated to core aspects of human language processing using different criteria in previous studies (Clos et al, 2013;Zaccarella and Friederici, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Fitch & Friederici, ). The approach of testing the ability to generate well‐formed hierarchical structures by acquiring the appropriate generative rules and applying them beyond the given perceptual stimuli has also been successfully used in the visual‐spatial, motor, and tonal domains (Jiang et al, ; Martins et al, , , ).…”
Section: Definitionsmentioning
confidence: 99%
“…In order to disambiguate between these components, it can be useful to look at domains with different auxiliary memory systems. For instance, during visual‐spatial and motor hierarchical processing, neither LIFG nor pSTS seemed to support hierarchical branching (Martins et al, , ). However, in these studies, the production of hierarchies was highly automatized.…”
Section: Neural Signatures Of Hierarchical Processingmentioning
confidence: 99%